The Effect of Naphthalene acetic acid (NAA) on cutting of Lignum Vitae ( Guaiacum officinale L. ) - วิเศษสุข, กฤษฎา; เทพสถิตย์, หทัยรัตน์; ดอกตาลยงค์, ประโยชน์; แสงมณี, ศิริพัน; รุ่นประพันธ์, อารยะ; โสขุมา, ถวิล; สุธรรมแปง, จิรพร; สุธรรมแปง, สาราญ; จิววิโรจน์, อัญชลี; พิทักษ์ตุลยา, พนิตานันท์ (Journal of Vocational Education in Agriculture, 2019)
The aim of this research was to find out the effects of NAA concentration on rooting of lignum vitae (Guaiacum officinael L.) stem cutting. Using Completely Randomized Design (CRD) consists 4 treatment, 4 replications; water supply (control), NAA at concentrations at 2,000, 4,000 and 6,000 ppm. Soaking lignum vitae stem cutting in each treatments for 30 minutes and put the stem cutting in to Seeding material (Sand:Burning husk:Coconut shell’s hair 1:2:1 ratio) in greenhouse shading for 60 days. The results showed that the stem cutting treated with NAA 6,000 ppm had the highest number of roots 5.10 roots and the percentage of rooting was highest 75 percent.